PHOSPHORUS ZONING FROM SECONDARY OLIVINE IN MANTLE XENOLITH FROM MIDDLE ATLAS MOUNTAINS (MOROCCO, AFRICA): IMPLICATIONS FOR CRYSTAL GROWTH KINETICS - Mavrogonatos, K.; Flemetakis, S.; Papoutsa, A.; Klemme, S.; Berndt, J.; Economou, G.; Pantazidis, A.; Baziotis, I.; Asimow, P.D. (Bulletin of the Geological Society of Greece, 2016)
Mantle xenolith samples in contact with basalt flows were collected from the Tafraoute maar in Morocco. Discrete melt veins are present in one xenolith sample, crosscutting primary layering and foliation. We used both optical microscopy and electron microprobe analysis to characterize the glasses and minerals in the melt veins. The melt veins consist of glass and crystals of olivine, clinopyroxene, plagioclase, spinel and apatite. The olivine in the melt veins is quite distinct from the same mineral within the matrix due to its characteristic P-enriched rims (up to 0.3 wt.%). Correlations between Al and P, as well as experimentally determined partition coefficient for P, point towards non-equilibrium partitioning during rapid crystal growth at the end of crystallization.